Charges de fond et suspensions transportees par les eaux d'ecoulement dans un petit bassin versant agricole sur pentes dans le Nord Vietnam - Orange, Didier; Phan, Ha Hai An; Lequeux, Brice; Henry des Tureaux, Thierry; Pham, Van Rinh; Tran Duc Toan (2007)
A small agricultural watershed on sloping lands (around 50 ha) in Northern Vietnam is equipped with 5 runoff measurement stations named weir. Each weir is representative of one vegetation cover (forest, fodder, cassava and old fallow). There is no relationship between bed load and rainfall amount due to a threshold process, but it is directly linked to the vegetation cover. In 2006, bed load losses are quite much important on the cassava crop (879 kg/ha/yr) than at the other weirs: 131 kg/ha/yr for old fallow, 83 kg/ha/yr for pluriannual plantation and 52 kg/ha/yr for forest. From some event measurements, the mean suspended load during the rising peak was a range 0.4-2.9 g/l with a SM peak around 3 to 8 g/l; the suspended load during the base flow was around 10-20 mg/l. It is impossible to predict the SM load with the discharge. For each weir, the best correlation is between SM load and Rindex emphasizing the duration and the amount of the rain event. The calculation of suspended load confirms the soil loss by suspended load is much more important than by bed load, even if the 95% of suspended load occurs during the peak events. On the whole watershed, the erosion amount by suspended load is 1.2 t/ha for 0.6 t/ha for bed load. More trees are in the basin, less is the suspended load; and at the opposite, the agricultural practices increase the amount of suspended load.